2004
DOI: 10.1167/iovs.03-1295
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associations of Epiretinal Membranes in Latinos: The Los Angeles Latino Eye Study

Abstract: ERMs occur frequently in Latinos, often bilaterally. The associations of ERMs with proliferative retinopathy, retinal lesions, macular holes, and cataract surgery were confirmed. Central PMF is associated with reduced visual acuity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
104
6
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(127 citation statements)
references
References 21 publications
11
104
6
6
Order By: Relevance
“…These authors speculated that the high prevalence of ERM in their Latino population was because of its high prevalence of diabetes. 9 In a large Epiretinal membranes in a Japanese population R Kawasaki et al ERM case series, 19 persons with diabetes were documented to be more likely to have bilateral involvement with idiopathic ERM than those without diabetes.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These authors speculated that the high prevalence of ERM in their Latino population was because of its high prevalence of diabetes. 9 In a large Epiretinal membranes in a Japanese population R Kawasaki et al ERM case series, 19 persons with diabetes were documented to be more likely to have bilateral involvement with idiopathic ERM than those without diabetes.…”
Section: Discussionmentioning
confidence: 96%
“…[6][7][8][9][10][11] It has been suggested that the higher prevalence in Hispanics as compared with other racial groups may be related to the higher frequency of diabetes in this racial/ethnic group. 9 In this report, we aim to describe the age-and genderspecific prevalence of ERM and associated risk factors in an adult Japanese population and to compare the prevalence rates with two other mainly white populations (the Blue Mountains Eye Study (BMES) in Australia and the Beaver Dam Eye study (BDES) in Wisconsin, USA) after age standardization to the world standard population.…”
Section: Introductionmentioning
confidence: 99%
“…Two types of epiretinal membranes were differentiated as described by Klein et al and Fraser-Bell and colleagues: 12,16 The first type consisted of a cellophane macular reflex only with a patch or patches of irregular increased reflection from the inner retinal surface. In the second type called premacular fibrosis, a greyish and opaque appearance of the inner retinal surface was combined with superficial retinal folds or traction lines.…”
Section: Methodsmentioning
confidence: 99%
“…11 Despite their clinical significance, there have been, besides a series of hospital-based studies, only six population-based investigations on the occurrence and associations of epiretinal membranes with other ocular and general parameters. [12][13][14][15][16][17] All these epidemiological studies were focused on whites, Hispanics or Japanese. Considering that China is the largest nation and that information about epiretinal membranes in the Chinese population is very scarce, it was the purpose of the present study to assess the prevalence of epiretinal membranes and their associations with ocular and general factors in Chinese as part of the Beijing Eye Study.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of ERM formation is 5.3% to 18.5% of 25 the population. [1][2][3][4] The first report of successful removal of ERM was published…”
Section: Okamoto Et Al -2-mentioning
confidence: 99%